Analysis of changes in PCSK9 and TNF-α concentrations in response to physical exercises using virtual reality in patients in the fifth stage of chronic kidney disease undergoing hemodialysis - Agnieszka Turoń-Skrzypińska; Alicja Mińko; Aleksandra Rył; Aneta Cymbaluk-Płoska; Maciej Domański; Kazimierz Ciechanowski; Iwona Rotter (BMC Nephrology)
Abstract Background The problem of reduced physical activity in patients with stage 5 Chronic Kidney Disease (CKD) is becoming more and more interesting in the medical community. One of the innovative solutions that can significantly increase patients’ motivation to exercise is the integration of physical training with virtual reality (VR) technology during hemodialysis. The aim of this study was to comprehensively assess the impact of regular physical activity using virtual reality on the concentration of plasma PCSK9 protein and TNF-α in patients with stage 5 CKD treated with hemodialysis. Methods A prototype of the NefroVR system was used in the research project. The study group consisted of patients who were entrusted with the task of conducting training using the prototype of the NefroVR system. Results In the conducted research, a significant decrease in PCSK9 protein and TNF-α concentration was observed in the study group after 3 months of exercises using virtual reality in hemodialysis patients. Conclusion Regular physical activity using innovative physiotherapy methods, such as virtual reality, contributes to the improvement of inflammatory parameters and may improve lipid homeostasis. Clinical trial number not applicable.